Light control of the peptide-loading complex synchronizes antigen translocation and MHC I trafficking - Jamina Brunnberg (Nature Portfolio, 2021)
Brunnberg et al. establish a protocol that enables them to optically control translocation of the transporter associated with antigen processing (TAP), which plays a role in delivering proteasomal degradation products into the ER lumen. Their versatile approach provides insights into TAP function in the context of peptide-loading complex and stable peptide-MHC I complex trafficking in living cells, but has the potential to be applied to the investigation of other pathways.